2015
DOI: 10.1038/srep11514
|View full text |Cite
|
Sign up to set email alerts
|

Charge deformation and orbital hybridization: intrinsic mechanisms on tunable chromaticity of Y3Al5O12:Ce3+ luminescence by doping Gd3+ for warm white LEDs

Abstract: The deficiency of Y3Al5O12:Ce (YAG:Ce) luminescence in red component can be compensated by doping Gd3+, thus lead to it being widely used for packaging warm white light-emitting diode devices. This article presents a systematic study on the photoluminescence properties, crystal structures and electronic band structures of (Y1−xGdx)3Al5O12: Ce3+ using powerful experimental techniques of thermally stimulated luminescence, X-ray diffraction, X-ray absorption near edge structure (XANES), extended X-ray absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(43 citation statements)
references
References 41 publications
2
36
2
3
Order By: Relevance
“…Belén et al 23 studied the interplay between the Ce Y and Y Al -Al Y in YAG by using the first-principles calculations and found that the presence of Y Al -Al Y could cause a strongly anisotropic expansion of the atomistic structure around the Ce Y impurities and decrease the effective ligand-field splitting of the 5 d 1 manifold, leading to the blue-shifts the two lowest Ce 3+ 4f–5d transitions. Although the photoluminescence properties of Ce 3+ ions in garnet structure were investigated24, the detailed relationship between the photoluminescence properties and the local structures as well as the distributions of activators in Ce 3+ -doped YAG phosphors have been rarely studied experimentally.…”
mentioning
confidence: 99%
“…Belén et al 23 studied the interplay between the Ce Y and Y Al -Al Y in YAG by using the first-principles calculations and found that the presence of Y Al -Al Y could cause a strongly anisotropic expansion of the atomistic structure around the Ce Y impurities and decrease the effective ligand-field splitting of the 5 d 1 manifold, leading to the blue-shifts the two lowest Ce 3+ 4f–5d transitions. Although the photoluminescence properties of Ce 3+ ions in garnet structure were investigated24, the detailed relationship between the photoluminescence properties and the local structures as well as the distributions of activators in Ce 3+ -doped YAG phosphors have been rarely studied experimentally.…”
mentioning
confidence: 99%
“…The excitation absorbed by the phosphor is excited from the 4f 1 ( 2 F 7/2 ) to 4f 0 5d 1 excited state, and the excited photons are emitted in the form of light and heat, respectively, with radiative recombination and non-radiative recombination. [27][28][29][30] According to the energy transitions above, the photons absorbed from the LD are excited from the 4f 1 (2F 7/2 ) ground state to 4f 0 5d 1 excited state and the excited photons are then relaxed to the 4f 1 (2F 7/2 ) ground state. The relaxation is divided into two types: non-radiative recombination (dotted line in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…В результате анализа рассчитанных плотностей электронных состояний были получены значения ширины запрещенной зоны в трех случаях: без оптимизации, с оптимизацией в рамках PM6 и PM7. Полученные результаты сравнивались с известным экспериментальным значением ширины запре-щенной зоны для YAG, равным по разным данным [1,3] порядка 7 эВ. Наиболее точный результат, 5,5 эВ, достигнут с использованием пространственной структуры, полученной в рамках метода PM7.…”
Section: расчет электронной структуры ячейки Yagunclassified
“…Гранаты -широко известный класс кристаллов, используемый в качестве люминофоров, твердо-тельных лазеров или сцинтилляторов [1]. Сцинтиллятор -это объект, преобразующий энергию ионизи-рующего излучения в фотоны оптического диапазона, которые могут быть легко зарегистрированы со-временными приемниками и обработаны электронной аппаратурой.…”
Section: Introductionunclassified